2014
DOI: 10.1371/journal.pone.0110005
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Thickness Correlates with the Presence and Severity of Angiographic Coronary Artery Disease in Stable Patients with Chest Pain

Abstract: ObjectiveEpicardial adipose tissue (EAT) is suggested to correlate with metabolic risk factors and to promote plaque development in the coronary arteries. We sought to determine whether EAT thickness was associated or not with the presence and extent of angiographic coronary artery disease (CAD).MethodsWe measured epicardial fat thickness by computed tomography and assessed the presence and extent of CAD by coronary angiography in participants from the prospective EVASCAN study. The association of EAT thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 26 publications
4
34
1
1
Order By: Relevance
“…Nevertheless, there is an emerging literature implicating pericardial fat in the pathogenesis of a variety of CV diseases 3740 . Here, we demonstrate pericardial fat is associated with incident CVD over long-term follow-up as well as cardiac structure, independent of selected measured influences of dysfunctional adiposity, defined by cardiometabolic risk factors, insulin resistance, inflammation, and imaging surrogates of hepatic fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is an emerging literature implicating pericardial fat in the pathogenesis of a variety of CV diseases 3740 . Here, we demonstrate pericardial fat is associated with incident CVD over long-term follow-up as well as cardiac structure, independent of selected measured influences of dysfunctional adiposity, defined by cardiometabolic risk factors, insulin resistance, inflammation, and imaging surrogates of hepatic fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Current understandings of the pathophysiology of EAT and atherosclerosis were strengthened by cross-sectional studies that revealed independent associations between increased EAT and the presence of CAD 9, 23, 24) . Moreover, several serial studies demonstrated that increased baseline EAT volume was associated with the progression or new development of coronary artery calcification (CAC).…”
Section: Discussionmentioning
confidence: 99%
“…Increased EAT is independently related to the presence and angiographic severity of CAD [8], a well as MACE [10]. Inflammatory infiltrations have been found in EAT in the areas near coronary lesions.…”
Section: Discussionmentioning
confidence: 91%
“…Increased EAT is related to the presence and angiographic severity of CAD [8] and coronary plaque vulnerability [9], and independently predicts major adverse cardiovascular events (MACE) [10].…”
Section: Introductionmentioning
confidence: 99%